Duration Prediction Models for Construction Projects in Middle East - El-Dash, K. M. M.; Ramadan, O. M. O.; Youssef, W. M. M. A. (Engineering, Technology & Applied Science Research, 2019)
Construction industry is one of the most influential motivators of a national economy. The success of construction projects is indispensable to sustain a robust economy. Completion time is important for construction projects, nevertheless project multifaceted objectives, sophisticated nature, inherent uncertainties, and risks are success impediments and can cause time overrun. Stochastic models and simulation scheduling techniques are developed to predict the risk and uncertainty effects on construction projects’ duration. The objective of this research is to develop models that predict the activity durations based on actual data from similar projects. The study introduces comprehensive statistical regression models using historical data of about 84,000 activities in Egypt, Kuwait, and Saudi Arabia. The activities encompass engineering, procurement and construction (EPC) activities for most disciplines of construction projects. The regression models can be utilized to predict more reliably the activities’ duration.